The sex-role identity, attributional style and self-esteem of a group of female students - Smit, Anel Leonie (Stellenbosch : University of Stellenbosch, 2008)
In this study the sex-role identities of 280 female students at Stellenbosch University were compared with regards to attributional style and self-esteem. Three self report questionnaires were used to measure the variables: The Bem Sex-Role Inventory, the Attributional Style Questionnaire and the Rosenberg Self-Esteem Scale. The results showed that the androgynous sex-role identity group had a significantly more optimistic attributional style and a higher degree of self-esteem than the feminine and undifferentiated groups. The results also showed a significant positive correlation between general attributional style and self-esteem. A pessimistic attributional style and a lower degree of self-esteem have been associated with a wide variety of psychological problems in research literature. The results of this study provide support for the theory that an androgynous sex-role identity might be significantly better than a feminine sex-role identity for the psychological health of women. The researcher suggests that the effects of traditional sex-role socialization on the psychological well-being of women should be considered in the planning of prevention and empowerment programs.